Fine particulate matter and risk of preterm birth and pre-labor rupture of membranes in Perth, Western Australia 1997-2007: A longitudinal study - Pereira, Gavin; Bell, M.; Belanger, K.; de Klerk, N. (Elsevier Ltd, 2014)
Objective: A recent longitudinal study reported an association between fine particulate (PM2.5) exposure and preterm birth (PTB) in a US cohort. We applied the same design to an Australian cohort to investigate associations with PTB and pre-labor rupture of membranes (PROM). Methods: From 287,680 births, we selected 39,189 women who had singleton births at least twice in Western Australia in 1997-2007 (n. = 86,844 births). Analyses matched pregnancies to the same women with conditional logistic regression. Results: For PROM adjusted odds ratios (ORs) for a 1µg/m3 increase in PM2.5 in the first trimester, second trimester, third trimester, and whole pregnancy were 1.00 (95% confidence interval (CI): 0.97, 1.03), 1.03 (95% CI: 1.00, 1.06), 1.02 (95% CI: 1.00, 1.05), and 1.02 (95% CI: 0.99, 1.05) respectively. For PTB, corresponding ORs were 1.00 (95% CI: 0.96, 1.04), 1.00 (95% CI: 0.96, 1.04), 0.98 (95% CI: 0.94, 1.02), and 0.99 (95% CI: 0.95, 1.04) respectively. Conclusion: Risk of PROM was greater for pregnancies with elevated PM2.5 exposure in the second trimester than were other pregnancies to the same Australian women at lower exposure. There was insufficient evidence for an association with PTB, indicating that a longer time period might be needed to observe an association if a causal effect exists. © 2014 Elsevier Ltd.